Unraveling abolition : legal culture and slave emancipation in Colombia / Edgardo Pérez Morales, University of Southern California. - Pérez Morales, Edgardo (Studies in legal history., 2022)
Unraveling Abolition tells the fascinating story of slaves, former slaves, magistrates and legal workers who fought for emancipation, without armed struggle, from 1781 to 1830. By centering the Colombian judicial forum as a crucible of antislavery, Edgardo Pérez Morales reveals how the meanings of slavery, freedom and political belonging were publicly contested. In the absence of freedom of the press or association, the politics of abolition were first formed during litigation. Through the life stories of enslaved litigants and defendants, Pérez Morales illuminates the rise of antislavery culture, and how this tradition of legal tinkering and struggle shaped claims to equal citizenship during the anti-Spanish revolutions of the early 1800s. By questioning foundational constitutions and laws, this book uncovers how legal activists were radically committed to the idea that independence from Spain would be incomplete without emancipation for all slaves.